Implementation Of User-Centered Design (UCD) Method On The Design Of Real- Time Coffee Shop Reservation Application - Dwi Nurul Huda; Sirait, Lisken; Fandhica, Ricke; Romdoni, Mochammad Rizki (Jurnal Bangkit Indonesia, 2025)
The digitalization of business has changed many aspects of life, including how coffee shops do business. In this context, SMS, WhatsApp, and Instagram technologies have become important tools in helping customers make reservations. Reservations at coffee shops allow customers to ensure a seat when visiting and avoid disappointment due to full coffee shops. At Samanko Coffee Roasters, reservations are made via WhatsApp, with customers contacting the contact listed on Samanko Coffee Roasters' Instagram account. This process involves several steps, including checking the availability of seats according to the customer's wishes and manual recording in a notebook. The problem that arises is the difficulty in identifying real-time seat availability and limitations in recording customer data. This can cause inconvenience and decrease customer satisfaction. The solution to this problem is the development of a Samanko Coffee Roasters reservation website using the User Centered Design (UCD) approach. The UCD approach places the user as the main focus in system design. The website interface can be customized according to user needs by involving users in the development process. Using the UCD method provides an effective solution based on usability evaluation using the SUS method on 20 respondents obtained a score of 87, meaning that the acceptance of the design is at level A or excellent.